Eleonora Pasotti, Resisting Redevelopment. Protest in Aspiring Global Cities, Cambridge, Cambridge University Press, 2020 - Gilles Pinson (Partecipazione e Conflitto, 2023)
For Book Reviews Abstract is not mandatory